1-Methylpyrene induces chromosome loss and mitotic apparatus damage in a Chinese hamster V79-derived cell line expressing both human CYP1A2 and sulfotransferase 1A1. (1st December 2020) - Yu, Hang; Li, Zihuan; Yang, Zongying; Song, Meiqi; Liu, Yungang
Abstract: 1-Methylpyrene (1-MP) is a ubiquitous environmental pollutant and rodent carcinogen. Its mutagenic activity depends on sequential activation by various CYP and sulfotransferase (SULT) enzymes. Previously we have observed induction of micronuclei and mitotic arrest by 1-MP in a Chinese hamster (V79)-derived cell line expressing both human CYP1A2 and SULT1A1 (V79-hCYP1A2-hSULT1A1), however, the mode of chromosome damage and the involvement of mitotic tubulin structures have not been clarified. In this study, we used immunofluorescent staining of centromere protein B (CENP-B) with the formed micronuclei, and that of β- and γ-tubulin reflecting the structures of mitotic spindle and centrioles, respectively, in V79-hCYP1A2-hSULT1A1 cells. The results indicated that 1-MP induced micronuclei in V79-hCYP1A2-hSULT1A1 cells from 0.125 to 2 μM under a 24 h/0 h (exposure/recovery) regime, while in the parental V79-Mz cells micronuclei were induced by 1-MP only at concentrations ≥ 8 μM; in both cases, the micronuclei induced by 1-MP were predominantly CENP-B positive. Following 54 h of exposure, 1-MP induced mitotic spindle non-congression and centrosome amplification (multipolar mitosis) in V79-hCYP1A2-hSULT1A1 cells, and anaphase/telophase retardation, at concentrations ≥ 0.125 μM with concentration-dependence; while in V79-Mz cells it was inactive up to 8 μM. This study suggests that in mammalian cells proficient in activating enzymes 1-MP may induce chromosome loss and mitotic disturbance, probably by interfering with the mitotic spindle and centrioles. Highlights: 1-Methylpyrene is potently aneugenic in metabolism-proficient mammalian cells. 1-Methylpyrene may disrupt mitotic apparatus by interfering with tubulin. 1-Methylpyrene may retard mitotic progression.